2016
DOI: 10.1182/asheducation-2016.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Biologic vs physiologic age in the transplant candidate

Abstract: Hematopoietic cell transplantation (HCT) remains a cornerstone of treatment of many hematologic malignancies but transplant-associated morbidity and mortality limit application to older patients. Biologic or chronologic age barriers to HCT have fallen, because patients in their 8th decade of life comprise the group with the greatest rise in transplant use over the past decade. Evaluating physiologic age or general health in older transplant candidates requires a systematic approach inclusive of functional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Clinical factors assessed for various subsets within the population with respect to survival included older age, previous HTx events, diabetic status, and BMI. These established risk factors were compared within subsets of third‐time cardiac graft recipients . There are characteristics of these cohorts that seem to demonstrate deviations from the previously reported findings of patients with third‐time HTx.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical factors assessed for various subsets within the population with respect to survival included older age, previous HTx events, diabetic status, and BMI. These established risk factors were compared within subsets of third‐time cardiac graft recipients . There are characteristics of these cohorts that seem to demonstrate deviations from the previously reported findings of patients with third‐time HTx.…”
Section: Discussionmentioning
confidence: 99%
“…We found those with a BMI above 30 at time of transplant (n = 7) had a 1‐, 5‐, and 10‐year survivability of less than half at all time points when compared to their counterparts with BMI under 30. Being overweight is an established risk factor that pertains to the third‐time HTx group also . One study found that substantial weight gain occurs following cardiac transplantation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment algorithms for severe aplastic anemia (SAA) are not well characterized for older patients. For older patients treatment decisions are based not only on disease factors but also on their health and functional ability to reduce the risk of treatment-related toxicity that may contribute to morbidity and mortality [1]. For these reasons hematopoietic cell transplantation (HCT) in older patients with SAA is usually only considered as second-line treatment [2].…”
Section: Introductionmentioning
confidence: 99%